2023
DOI: 10.1155/2023/3906043
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Improves Diabetic Cardiomyopathy by Inhibiting Pyroptosis through AKT/Nrf2/ARE Pathway

Abstract: This study is aimed at exploring whether curcumin can regulate the AKT pathway, promote the transfer of Nrf2 into the nucleus, and inhibit cell pyroptosis in diabetic cardiomyopathy. Diabetic rats and cardiomyocytes were treated with curcumin to study its effect on myocardial pyroptosis. Whether curcumin can promote the transfer of Nrf2 into the nucleus through AKT pathway regulation was assessed by western blotting and immunofluorescence. The Nrf2 knockout vector and ml385 were used to block the Nrf2 pathway,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…A cellular model of doxorubicin‐induced cardiotoxicity was established by co‐incubating H9c2 cells with doxorubicin at a concentration of 1 μM. The concentration of nigericin (an activator of NLRP3) used in the experiments was 10 μM, which has been confirmed in previous studies 23 …”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…A cellular model of doxorubicin‐induced cardiotoxicity was established by co‐incubating H9c2 cells with doxorubicin at a concentration of 1 μM. The concentration of nigericin (an activator of NLRP3) used in the experiments was 10 μM, which has been confirmed in previous studies 23 …”
Section: Methodssupporting
confidence: 52%
“…Bardoxolone methyl (10 mg/mL) dissolved in dimethyl sulfoxide (DMSO) was administered weekly by ip injection (10 mg/kg body weight) for 6 weeks 22 . Additionally, ML385 (5 mg/mL) dissolved in DMSO was administered weekly by ip injection (20 mg/kg body weight) for 6 weeks 23 . Animals that served as controls were injected with the same volume of DMSO or normal saline alone.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of NLRP3, caspase-1, IL-18, and IL-1b was also significantly increased. Meanwhile, DM rats treated with ML385 to suppress Nrf2 showed more severe myocardial fibrosis and cardiac enlargement (101). All of these studies provide valuable evidence that the Nrf2-related pathway may serve as a future target for treating DCM.…”
Section: Nrf2-related Pathwaysmentioning
confidence: 77%
“…In a rat model of SD diabetes established by HFD and intraperitoneal injection of STZ, curcumin (200 mg/kg/d) treatment for 8 months promoted the transfer of Nrf2 to the nucleus through the AKT pathway, increased the expression of the antioxidant factors HO-1 and GCLC, reduced the accumulation of mitochondrial ROS, and mitigated mitochondrial oxidative damage. The study suggests that curcumin inhibits cell apoptosis by activating the AKT/Nrf2/ARE pathway and eliminates the accumulation of superoxide in myocardial cells ( Wei et al, 2023 ). Additionally, Yao et al research has shown that curcumin can upregulate the expression of AMPK and JNK1 to stimulate mitophagy, as well as upregulate the expression of Bcl-2 and Bim to reduce cardiomyocyte apoptosis.…”
Section: Plant Secondary Metabolites-based Diabetes Cardiomyopathy Ta...mentioning
confidence: 99%